2022
DOI: 10.1038/s41598-022-16396-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite, protein, and tissue dysfunction associated with COVID-19 disease severity

Abstract: Proteins are direct products of the genome and metabolites are functional products of interactions between the host and other factors such as environment, disease state, clinical information, etc. Omics data, including proteins and metabolites, are useful in characterizing biological processes underlying COVID-19 along with patient data and clinical information, yet few methods are available to effectively analyze such diverse and unstructured data. Using an integrated approach that combines proteomics and met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 176 publications
3
13
0
Order By: Relevance
“…Overall, clustering and enrichment results are in agreement with what is known about SARS-CoV-2 influencing the host’s processes, i.e., targeting and disrupting gene transcription host mRNA facilitation and transcription factor activity (Clusters 3 and 4) [ 59 ], disruptions in metabolite production (Cluster 1) [ 69 ], and hijacking the cell’s vesicle transport system (Cluster 6). What is more, they provide a potential molecular basis for these effects, as they seem to be primarily focused on the NE-localized proteins of the virus.…”
Section: Resultssupporting
confidence: 80%
“…Overall, clustering and enrichment results are in agreement with what is known about SARS-CoV-2 influencing the host’s processes, i.e., targeting and disrupting gene transcription host mRNA facilitation and transcription factor activity (Clusters 3 and 4) [ 59 ], disruptions in metabolite production (Cluster 1) [ 69 ], and hijacking the cell’s vesicle transport system (Cluster 6). What is more, they provide a potential molecular basis for these effects, as they seem to be primarily focused on the NE-localized proteins of the virus.…”
Section: Resultssupporting
confidence: 80%
“…This result is in accordance with the above taxonomical analysis and the increase of species related to putrefactive dysbiosis. Remarkably, several public studies highlighted the possible correlation between COVID‐19 disease severity and the alteration of systemic amino acid metabolism (Masoodi et al, 2022 ; Paez‐Franco et al, 2021 ; Rahnavard et al, 2022 ). In particular, the enrichment of specific amino acids, such as arginine and proline, could contribute to excessive systemic inflammation and a consequent increase in the severity of the disease (Rahnavard et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, several public studies highlighted the possible correlation between COVID‐19 disease severity and the alteration of systemic amino acid metabolism (Masoodi et al, 2022 ; Paez‐Franco et al, 2021 ; Rahnavard et al, 2022 ). In particular, the enrichment of specific amino acids, such as arginine and proline, could contribute to excessive systemic inflammation and a consequent increase in the severity of the disease (Rahnavard et al, 2022 ). Therefore, the increased protein metabolic capability of the intestinal microbiome observed in this study could suggest the intestinal bacterial communities' contribution to systemic inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the non-COVID-19 and healthy groups, the 15-HETE levels identified in the COVID-19 individuals were significantly depleted. The lack of anti-inflammatory signals brought on by the reduction of 15-HETE may be a factor in the increased inflammation observed during COVID-19 infection [ 172 ]. A targeted metabolomic study analyzed and identified AMP, dGMP, sn-glycerol-3-phosphocholine, and carnitine metabolites that were dysregulated in patients with COVID-19 [ 173 ].…”
Section: Metabolomics Covid-19 and Kidney Injurymentioning
confidence: 99%